2020
DOI: 10.1089/thy.2019.0052
|View full text |Cite
|
Sign up to set email alerts
|

Whole-Exome Sequencing of Matched Primary and Metastatic Papillary Thyroid Cancer

Abstract: Background: Distant metastasis is a rare occurrence in thyroid cancer, and it can be associated with poor prognosis. The genomic repertoires of various solid malignancies have previously been reported but remain underexplored in metastatic papillary thyroid cancer (PTC). Furthermore, whether distant metastases harbor distinct genetic alterations beyond those observed in primary tumors is unknown. Methods: We performed whole-exome sequencing on 14 matched distant metastases, primary PTC tumors, and normal tissu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 76 publications
(68 reference statements)
1
32
0
Order By: Relevance
“…A discordant mutational status between the primary site and the metastases supports this mechanism and it was recorded in several human tumors (including lung, melanoma, colorectal, gastric, breast) [4]. In TC, discordant patterns were reported for BRAF V600E , TERT, RAS and other mutations [27,39,40,51,52,[58][59][60][61][62][63][64][65]. Data related to PTC are reviewed in Table 3.…”
Section: Discordant Mutational Status Between Primary Site and Metastmentioning
confidence: 83%
See 1 more Smart Citation
“…A discordant mutational status between the primary site and the metastases supports this mechanism and it was recorded in several human tumors (including lung, melanoma, colorectal, gastric, breast) [4]. In TC, discordant patterns were reported for BRAF V600E , TERT, RAS and other mutations [27,39,40,51,52,[58][59][60][61][62][63][64][65]. Data related to PTC are reviewed in Table 3.…”
Section: Discordant Mutational Status Between Primary Site and Metastmentioning
confidence: 83%
“…Interestingly, the two selected areas of the primary tumor and the two selected areas of on regional metastasis presented similar genetic profiles, whereas the two selected areas of another regional metastasis had more divergent mutations and fusions [55]. Striking heterogeneity was also observed between paired primary tumors and metastases in studies done by means of NGS and WES studies [58,60,63,64]. Mass spectrometry imaging lymph node discordant Gawin et al 2019 [65] Legend: * for likely pathogenic cancer genes.…”
Section: Discordant Mutational Status Between Primary Site and Metastmentioning
confidence: 99%
“…used whole-exome sequencing to compare 14 trios of matched distant metastasis, primary PTC tumors and normal samples. Those authors found striking heterogeneity between the primary PTC tumors and metastatic specimens, attributed mainly to passenger mutations ( 19 ). In comparison to those studies, our study population is more heterogeneous and reflects real life practice in a tertiary hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies have addressed this question, employing different approaches and reaching diverse conclusions ( 16 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…In previous attempts, we succeeded in deriving novel markers for follicular thyroid tumors, in samples analyzed previously by microarray and qPCR [62,63]. It also cannot be excluded that metastatic spread in certain tumors is a stochastic event, or the changes are late and discriminable only when distant metastasis tissue is accessible [64]. In any of these scenarios, we cannot abandon the approaches to search for molecular predictors, as the clinically known PTC features are not sufficient to predict patient outcome in full [7].…”
Section: Discussionmentioning
confidence: 99%